2001
DOI: 10.1061/(asce)0733-947x(2001)127:3(254)
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Distress on Flexible Pavements Using Variable Tire Pressure

Abstract: ABSTRACT:The potential of variable tire pressure technology to 1ninimize distress on flexible pavements with thin asphalt surfacing layers and peat soil subgrade was evaluated using in-situ stress-strain data. Pavement interfacial strains and corresponding subgrade stresses imposed by a three-axle truck were measured and used to estimate the fatigue life of the surfacing layer. Three levels of tn1ck wheel loads in combination with four tire inflation pressures (350 , 490 , 630 , and 770 kPa) were used to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 12 publications
2
32
0
1
Order By: Relevance
“…Another Irish study concluded that haulage trucks with systems for managing variable tire pressure such as CTIS can minimise distress on flexible pavements with thin asphalt surfacing layers and peat soil subgrade. This may therefore enhance the serviceability of pavements overlying peat or other soil foundations (Owende et al 2001). The latter study also indicated that there is evidence to show an empty truck with high tire inflation pressure (770 kPa) will induce as much fatigue damage to the road pavement as a fully laden truck that is operated at low (350 kPa) tire inflation pressure (Owende et al 2001).…”
Section: Impacts Of Ctismentioning
confidence: 95%
See 2 more Smart Citations
“…Another Irish study concluded that haulage trucks with systems for managing variable tire pressure such as CTIS can minimise distress on flexible pavements with thin asphalt surfacing layers and peat soil subgrade. This may therefore enhance the serviceability of pavements overlying peat or other soil foundations (Owende et al 2001). The latter study also indicated that there is evidence to show an empty truck with high tire inflation pressure (770 kPa) will induce as much fatigue damage to the road pavement as a fully laden truck that is operated at low (350 kPa) tire inflation pressure (Owende et al 2001).…”
Section: Impacts Of Ctismentioning
confidence: 95%
“…This may therefore enhance the serviceability of pavements overlying peat or other soil foundations (Owende et al 2001). The latter study also indicated that there is evidence to show an empty truck with high tire inflation pressure (770 kPa) will induce as much fatigue damage to the road pavement as a fully laden truck that is operated at low (350 kPa) tire inflation pressure (Owende et al 2001). Stuart et al (1987) indicated that the road life can be shortened or extended depending on the quality of the vehicle travelling, which can indicate that the road life will increase in the case of application of CTIS technology.…”
Section: Impacts Of Ctismentioning
confidence: 99%
See 1 more Smart Citation
“…Its addition reduces the heat production during hydration and limits the need for additional additives [18]. One application of RoadCem in concrete is thin hybrid layers (THL) which is a pavement product constructed underneath an asphalt or bitumen surface layer [14,19,20]. THL materials are flexible with a high dynamic elastic modulus, compressive and flexural strengths, and breaking strain without the problems associated with standard concretes, including shrinkage, rate of curing, and frequency of joints, thinner with a faster time for traffic loading.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper describes a full scale accelerated loading performance test on a 20mm Dense Base Coarse Macadam [6] which overlaid a peat based forest access roads [5]. Such forest roads generally have a weak pavement structure, which consists of a surface dressed granular base and a subbase (±0.5m deep) that overlay deep peat foundations.…”
Section: Introductionmentioning
confidence: 99%